2001
DOI: 10.3138/8741-g618-5601-1125
|View full text |Cite
|
Sign up to set email alerts
|

DEM Manipulation and 3-D Terrain Visualization: Techniques Used by the U.S. National Park Service

Abstract: Manipulating digital elevation model (DEM) surfaces, like pliable modelling clay, enhances the appearance and legibility of 3-D topography on maps. The U.S. National Park Service (NPS) uses the familiar image-editing tools in Adobe Photoshop to manipulate raster DEM data. Exporting modified DEM data with the help of freeware and shareware utilities allows subsequent rendering of final 3-D scenes in Corel Bryce. Techniques to be discussed include topographic substitution – a method for reverse engineering pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 4 publications
0
25
0
2
Order By: Relevance
“…Because it has been shown that 3D-visualization stimulates interest and is more easily understood by people not familiar with complicated topographic maps or DEMs [e.g., Patterson 2001;Drogue et al 2002;Sidiropoulos and Vasilakos 2006;Leuthold et al 2007], APIA felt that this was an important part of telling the Belkofski story. With new advances in 3D-modeling and the availability of free software to produce 3D-visualizations the ability to integrate ethnographic data with a GIS is possible for a wide range of uses.…”
Section: Resultsmentioning
confidence: 99%
“…Because it has been shown that 3D-visualization stimulates interest and is more easily understood by people not familiar with complicated topographic maps or DEMs [e.g., Patterson 2001;Drogue et al 2002;Sidiropoulos and Vasilakos 2006;Leuthold et al 2007], APIA felt that this was an important part of telling the Belkofski story. With new advances in 3D-modeling and the availability of free software to produce 3D-visualizations the ability to integrate ethnographic data with a GIS is possible for a wide range of uses.…”
Section: Resultsmentioning
confidence: 99%
“…Since then terrain generalisation, the discipline that aims at removing unnecessary and distracting details from DEMs to accentuate important landforms, has produced several works where cartographers first extract important landscape features or simplify the terrain, and then proceed with the visualisation phase (Jenny, 2001;Jenny et al, 2011;Leonowicz et al, 2012;Guilbert et al, 2014). Other techniques involved the overlay of several images, either obtained by illuminating the scene from different angles or by using DEM derivatives, to obtain shaded reliefs where ridges and channel are enhanced (Patterson, 2001a;Patterson, 2001b;Patterson and Hermann, 2004;Loisios et al, 2007;Kennelly, 2008;Patterson, 2013). Jenny (2001) used an interactive process to locally change the light source, coupled with several other techniques to simulate all the aspects of manual shading.…”
Section: Introductionmentioning
confidence: 99%
“…A small-scale shaded relief with many intricate terrain details can inhibit the perception of the main landforms (for example, main ridges and valleys). As Patterson (2001a) notes, the dense details obscure macro topography-it is impossible to see the forest for the trees. Nowadays, when highly detailed elevation data are abundant and freely available, conducting research to automate the removal of unwanted details from terrain is highly relevant.…”
Section: R E P L a C E W O R D C L O U Dmentioning
confidence: 99%
“…Although simple methods exist to remove local irregularities from terrain (for example, low-pass ltering), they also apply smoothing to important ridges and valley edges, solving one problem but creating another. More sophisticated methods, speci cally developed for simplifying terrain models for relief shading, are not implemented in commercial software, and therefore rarely used (Weibel 1992, Böhm 2000, Prechtel 2000, Patterson 2001b, c, Leonowicz et al 2010 Figures 1 and 2 compare manual and automated shaded relief of the same geographic areas. Digitally shaded relief is often not successful at portraying the main structures of a terrain at medium and small scales.…”
Section: R E P L a C E W O R D C L O U Dmentioning
confidence: 99%